Dynamics of Employee Engagement in Psychology Bureau Companies - istiqomah, Istiqomah; Hardew, Ayatullah Kutub (Psikoborneo: Jurnal Ilmiah Psikologi, 2024)
Employee engagement is the commitment of employees to perform corporate tasks to achieve their goals, this commitment is in the form of employee involvement in work duties involving work roles, physical, cognitive and emotional conditions. Employees with corporate engagement are usually tied to companies that are in government agencies, large companies that are still in government agencies. Meanwhile, many private companies have unique work systems such as the X psychology bureau, which operates in the field of service providers for psychological services, especially in the field of organizational industry. The X psychology bureau requires a high employee commitment to the company's performance system referring to the project as agreed with the client, so employees will have a flexible work system following the client's demands. This research aims to find out the dynamics of employee engagement in X's psychology bureau which makes employees willing to work for the company. This study used a qualitative method of phenomenology type, with three main subjects in depth and one significant tothers, data analysis in this study using the Interpretative Phenomenologic Analysis (IPA) method. The results of this study show employees have engagement in the company due to support, facilities provided by companies such as a positive working environment, development of employees' self-potential by providing projects according to employees' working styles and being able to prepare employees for career. This study was able to provide implications for subsequent research to be able to develop and explore the theme of engagement at a company's psychology bureau that has a unique work system referring to a project based on an agreement with the client.Employee engagement merupakan komitmen karyawan dalam menjalankan tugas perusahaan untuk mencapai tujuannya, komitmen karyawan ini berupa keterlibatan karyawan dalam menjalankan tugas kerja yang melibatkan peran kerja, kondisi fisik, kognitif dan emosi. Karyawan yang memiliki engagement pada perusahaan biasanya terikat dengan perusahaan yang berada diinstansi pemerintah, perusahaan besar yang masih berada di instansi pemerintahan. Sementara itu banyak perusahaan swasta yang memiliki sistem kerja yang unik seperti pada biro psikologi X yang bergerak pada bidang penyedia jasa untuk layanan psikologi khususnya dalam bidang indutri organisasai. Biro psikologi X memerlukan komitmen karyawan yang tinggi untuk sistem kinerja perusahaan yang mengacu pada projek sesuai kesepakatan dengan klien, sehingga karyawan akan memiliki sistem kerja yang fleksibel mengikuti permintaan klien. Penelitian ini bertujuan untuk mengetahui dinamika employee engagement pada perusahaan biro psikologi X yang membuat karyawan bersedia bekerja diperusahaan. Penelitian ini menggunakan metode kualitatif jenis fenomenologi, dengan tiga subjek utama secara mendalam dan satu significant others, analisis data pada penelitian ini menggunakan metode Interpretative Phenomenologic Analysis (IPA). Hasil dari penelitian ini menunjukan karyawan memiliki engagement pada perusahaan karena terdapat dukungan, fasilitas yang diberikan oleh perusahaan seperti lingkungan kerja yang positif, pengembangan potensi diri karyawan dengan memberikan projek sesuai dengan gaya bekerja karyawan serta mampu mempersiapkan karyawan untuk ke jenjang karier. Penelitian ini mampu memberikan implikasi kepada penelitian selanjutnya untuk mampu mengembangkan dan menggali tema engagement pada perusahaan biro psikologi yang memiliki sistem kerja yang unik mengacu pada projek berdasarkan kesepakatan dengan klien.